Long‐term outcome of multiple joint procedures in haemophilia. (28th October 2013) - de Kleijn, P.; Sluiter, D.; Vogely, H. Ch.; Lindeman, E.; Fischer, K.
Summary: In elderly people with haemophilia (PWH), surgery of more than one joint of the lower extremities might be needed. Multiple joint procedures (MJP) were introduced in 1995, defined as any combination of Total Knee or Total Hip Arthroplasty or Ankle Arthrodesis during one in‐hospital stay. The expectation is that by means of such procedures this specific population is able to physically function better for an extended period of time. Thus, they will participate in their society in an optimal way. In this study, we tried to describe an outcome after MJP, including pre‐ and post‐operative pain and range of motion (ROM), and recommend measurement tools. 22 of 37 PWH who underwent MJP between 1995 and 2012 were available for assessment. Pain (WFH score) and range of motion were compared pre and postoperatively. Current outcome was described by VAS per joint, nocturnal and overall pain, MACTAR, Hemophilia Activity List, SF36, and EQ‐5D. Mean age at surgery was 50, 3 years (SD 8, 3); mean follow‐up 12 years (1–18 years). Pain (VAS) decreased post‐surgery (Median 1 – 1, 5), but moderate pain remained. Extension of knees slightly increased, but both knee flexion and ankle plantar and dorsal flexion decreased. PWH reported the ability to stand longer but also pointed at specific problems, e.g. riding a bike (MACTAR). The HAL showed limited activities (functional domains), especially in the 'complex lower extremity' (22, 8/100). The SF36 and EQ‐5D showed a mix of physical problems of our population, while experiencing moderate pain and reasonable physical functioning. This led us to the conclusion that adequate follow‐up is needed: ROM of all joints, VAS of all joints as well as nocturnal and overall pain, HAL, SF36 and EQ5D. Performance based activities and participation need further attention.